Analyzing Joinery for Furniture Designed for Disassembly - Maciej Sydor; Kacper Stańczyk (Journal of Manufacturing and Materials Processing)
End-users can design personalized furnishing products using remote web-based CAD systems. However, if these designs fail to incorporate design for disassembly (DfD) principles, the furniture’s subsequent repair, reconfiguration, recycling, and disposal can be significantly hindered. To address this drawback, this study supports DfD, a strategy that enables the creation of easily repairable, reusable, and recyclable furniture to reduce waste and environmental impact. Consequently, this review aims to classify and evaluate available furniture joinery systems for their suitability within DfD frameworks, ultimately promoting their implementation within CAD environments. To this end, various solutions were evaluated, including traditional joints, dowel/biscuit, hammered, directly screwed, snap-on, expandable, and cam/bolt fasteners. Based on a literature review and practical observations, the analyzed joinery systems were categorized into non-disassemblable, conditionally disassemblable, and fully disassemblable categories. Only the fully disassemblable solutions effectively align with DfD principles. The study postulates a preference for expandable and cam/bolt fasteners in furniture designs, noting that although snap-on fasteners can potentially support DfD, this outcome is not always ensured. To guarantee that the designed furniture adheres to the DfD principles, the following eight furniture design guidelines were formulated: develop web-accessible disassembly instructions, prioritize access to fast-wearing components, prioritize modularity, standardize parts in modules, label components, enable independent component removal, use materials that withstand repeated disassembly, and employ fully disassemblable joints.